PENGARUH ERA POST-TRUTH BAGI PEMBELAJAR BAHASA ASING: KAJIAN FILOSOFIS-FENOMENOLOGIS FENOMENA ERA POST-TRUTH DALAM DUNIA PEMELAJARAN BAHASA JERMAN DAN INGGRIS TINGKAT DASAR - Dian Rizky Azhari (Jurnal SORA, 2019)
The Post-truth era brought negative influences to all aspects of modern society, including the field of foreign language studies. These influences get into people's lives through the consciousness of each individual and influencing their ideology. Using an approach to critical discourse analysis and phenomenological philosophy analysis, this paper explains how the Post-truth climate enters consciousness and influencing every individual action, especially in the case of foreign language studies. The results are found that this Post-truth era affects two aspects of foreign language studies: language aspect and cultural aspect. This influence can only be prevented through the active role of both the learner and the instructor of the foreign language. It is hoped that this paper will be able to explain the situation of learning foreign languages in the midst of the Post-truth climate and offer solutions to overcome them.